Penerapan Merdeka Belajar-Kampus Merdeka Dalam Pembelajaran Pendidikan Agama Islam: Integrasi Proyek Sosial Dan Pengembangan Karakter Islami Di Sekolah - Al Imron, Muhammad; Agus Pahrudin; Agus Jatmiko; Koderi (AL MURABBI, 2024)
Abstract: The implementation of Independent Learning-Independent Campus (MBKM) in Islamic Religious Education (PAI) has opened up opportunities to integrate social projects that support the development of students' Islamic character. This article aims to explore the implementation of MBKM in PAI, focusing on the integration of social projects and Islamic character development. Through a qualitative approach with a case study method, this study involved teachers, students, principals, and parents of students in several schools that implement MBKM. The results of the study indicate that the integration of social projects in PAI learning not only increases students' social awareness but also helps them internalize religious values in real contexts. By involving students in social projects, they can develop attitudes of empathy, responsibility, and social concern, all of which contribute to the formation of a solid Islamic character.